(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In recent years, the industry has seen a surge in technology-driven start-ups that have disrupted traditional business models and transformed the way people travel. Innovative solutions such as online booking platforms, travel apps, and AI-driven customer service tools have created new opportunities for entrepreneurs to provide personalized and convenient travel experiences. The travel and tourism sector is one of most dynamic and expanding markets in the world. This article discusses a study in the field of tourism and hospitality that utilized exploratory research methods to answer questions related to an unfamiliar research topic. The study employed a sample strategy specifically developed for this purpose and collected data from human resource and training managers in four and five-star hotels in Chandigarh, Jalandhar, and Amritsar, India. A structured questionnaire was used to collect data on both demographic variables and responses related to the research problem. The results of the study provide valuable insights into the challenges and opportunities present in the tourism and hospitality industry, with certain skills like customer service and risk-taking ability being identified as particularly important for success. The study also highlights some major challenges facing the industry, including a perceived lack of government support and issues with unpredictable business and harsh regulations. The findings can be used by individuals and organizations in the tourism and hospitality industry to better understand the key factors that contribute to success and the challenges that must be addressed.